Circulating thyroxine, thyroid-stimulating hormone, and hypothyroid status and the risk of prostate cancer. - Alison M Mondul; Stephanie J Weinstein; Tracey Bosworth; Alan T Remaley; Jarmo Virtamo; Demetrius Albanes (PLoS ONE)
Background Thyroid hormones may influence risk of cancer through their role in cell differentiation, growth, and metabolism. One study of circulating thyroid hormones supports this hypothesis with respect to prostate cancer. We undertook a prospective analysis of thyroid hormones and prostate cancer risk in the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) Study. Methods Within the ATBC Study, a randomized controlled trial of α-tocopherol and β-carotene supplements and cancer incidence in male smokers, 402 prostate cancer cases were sampled. Controls were matched 2:1 to cases on age and date of blood collection. Odds ratios (OR) and 95% confidence intervals (CI) of prostate cancer were estimated for quintiles of serum total and free thyroxine (T4), thyroid-stimulating hormone (TSH), thyroid-binding globulin (TBG), and by categories of thyroid status. Results Men with serum higher TSH had a decreased risk of prostate cancer compared to men with lower TSH (Q5 vs. Q1-4: OR = 0.70, 95% CI: 0.51-0.97, p = 0.03). When the T4 and TSH measurements were combined to define men as hypothyroid, euthyroid or hyperthyroid, hypothyroid men had a lower risk of prostate cancer compared to euthyroid men (OR = 0.48, 95% CI = 0.28-0.81, p = 0.006). We observed no association between hyperthyroid status and risk, although the number of hyperthyroid men with prostate cancer was small (n = 9). Conclusions In this prospective study of smokers, men with elevated TSH and those classified as being in a hypothyroid state were at decreased risk of prostate cancer. Future studies should examine the association in other populations, particularly non-smokers and other racial/ethnic groups.